Correction: A systematic review verified by bioinformatic analysis based on TCGA reveals week prognosis power of CAIX in renal cancer. - Zikuan Zhang; Bo Wu; Yuan Shao; Yongquan Chen; Dongwen Wang (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0278556.].